Perilaku Penggunaan Smartphone dan Akses Pornografi di Kalangan Remaja Perempuan - Rachmaniar Rachmaniar; Puji Prihandini; Preciosa Alnashava Janitra (Program Studi Ilmu Komunikasi FISIP Universitas Syiah Kuala, 2018)
This study aims to determine the use of smartphones and how these technologies allow access to pornography among junior high school girls. Using a qualitative descriptive study method, this study examines ownership of smartphones and pornographic content that may be accessed via smartphones. The informants were four students of SMP Negeri 2, Padalarang, West Java. Data collection was conducted through in-depth interviews and observation. The results showed that junior high school students started to have regular mobile devices since they were still in elementary school. After they began to use smartphones at junior high school, they were inadvertently exposed to the pornographic content. These findings reveal that how more sophisticated technological devices have the potential to open access to pornographic content.